Germany and China: How Entanglement Un-dermines Freedom, Prosperity and Security By Andreas Fulda London etc.: Bloomsbury Academic, 2024. 256 pp. ISBN: 9781350357044: by Andreas Fulda - Weigelin-Schwiedrzik, Susanne (Journal of the European Association for Chinese Studies, 2025)
Germany and China: How Entanglement Undermines Freedom, Prosperity and Security By Andreas Fulda London etc.: Bloomsbury Academic, 2024. 256 pp. ISBN: 9781350357044